THE APPLICATION OF DIGITAL MARKETING AS A PRODUCT MARKETING STRATEGY UD. BINTANG ANTIK SEJAHTERA - Nurani; Eldon, Mokhamad; Eka Titis Rahmawati (BEMJ : Business, Entrepreneurship, and Management Journal, 2024)
Currently internet technology has developed rapidly in society. Digital marketing strategies are an alternative way for businesses to reach consumers very broadly and quickly in promoting their products via the internet and to increase sales volume. Digital marketing strategies use media such as websites, social media, databases, as well as digital audio and video to reach a wider audience. The purpose of this study was to determine the application of digital marketing strategy as a product marketing strategy for UD Bintang Antik Sejahtera which can increase its sales turnover as measured using the SWOT matrix. This research was conducted using a descriptive qualitative approach using the IFAS Matrix, EFAS Matrix, and SWOT Matrix to measure strengths, weaknesses, opportunities and threats. Source of data obtained from primary data and secondary data. Data collection techniques through interviews and documentation. The results of this study indicate that the implementation of digital marketing strategies has been successfully implemented through websites, social media, as well as digital audio and video so that there has been an increase in turnover. From the results of the IFAS matrix, it is strong in identifying internal factors, the EFAS matrix is good at responding to existing opportunities and avoiding threats that come from competitors.